Ovarian abscess with spontaneous vaginal drainage - Souza, Gustavo A. de (São Paulo Medical Journal, 1997)
The occurrence of a rare ovarian abscess, spontaneously drained through the vagina after an abdominal hysterectomy is described.The treatment was an oophorectomy.The various forms of primary ovarian abscess are discussed in connection with these observations. This case illustrates the need for adequate manipulation of the gonad during pelvic surgery in order to avoid parenchymal contamination and the subsequent formation of such abscesses.